EFFECT OF CONJUNCTIVA-LIMBUS TRANSPLANTATION WITH FIBRIN GLUE COMPARE TO SUTURE TECHNIQUE ON STABILITY OF THE GRAFT ATTACHMENT IN PTERYGIUM SURGERY - Sutyawan, E; Niti, S; Widiana, and R (BALI MEDICAL JOURNAL; Volume 2 Number 1, January-April 2013, 2013)
Objective: Pterygium is a growth that develops on the conjunctiva or mucous membrane covers the white part of eye. It is a benign or noncancerous growth that is often shaped like a wedge. This study aims to assess the efficacy and safety attachment graft on conjunctiva-limbus autograft transplantation using fibrin glue compared with suture technique in pterygium patient. Method : Single-blind randomized clinical trials. The samples were all pterygium patients with grade two or more who underwent pterygium surgery at the eye clinic and central operating theatre Sanglah General Hospital Denpasar, Bali-Indonesia and met the eligibility criteria. Samples were divided into suture and fibrin glue groups based on permutation-block randomization. Mann-Whitney U test and repeated measurement of ANOVA Analyses were performed to determine the different between two treatments. Results : There were no significant differences in the stability of graft’s attachment between the two groups either on the first day, first week and first month despite fibrin glue technique showed lower results in the first week and first month ( p = 0.787, p = 0.233, and p = 0.475). The average time it takes the fibrin glue technique 21.80 ± 2:37 minutes, much shorter than 41.67 ± 6.99 min in the suture technique ( p = 0.001). Postoperative comfort in the fibrin glue group showed lower scores on the first day, first week and first month compared with the suture group ( p = 0.000, p = 0.000 and p = 0.035). During the follow-up period no complications were found. Conclusion: The stability of graft attachment between the fibrin glue and suture technique is not significantly different.  Fibrin glue could be chosen as an alternative method in the conjunctiva-limbus autograft and helpful in shortening the operating time and improve comfort postoperatively.
Keywords: conjunctiva-limbal auto graft, fibrin glue, graft stability